On DNA modelling : interaction of a double helicoidal structure with viscous bio-fluid - Shu, Jian Jun (2011)
The paper aims at extending, utilising and generalising research in nonlinear dynamics of (i) spiral/helicoidal structures, and (ii) viscous, low speed fluid to biomechanical DNA fluidstructure